HOLOCENE CLIMATIC AND ENVIRONMENTAL CHANGES IN THE ARID AND SEMI-ARID AREAS OF CHINA: A REVIEW - Feng Z.-D.; Wang H.B.; An C.B. (My University, 2006)
This paper reviews recently published literature, most of which was published in Chinese, and searches for regional patterns of Holocene changes useful in depicting global patterns. The Holocene in the Xinjiang region can be divided into three stages: a warming and dry early stage (from 11 10 to 8-7 ka BP), a warm and wet middle stage (from 8-7 to 4.5-3 ka BP) and a fluctuating cool and dry late stage (since 4.5-3 ka BP). The Holocene in the northern Tibetan Plateau can also be divided into three stages: a warming and wet stage (from 10.5-10 to 5-4 ka BP), followed by a variable drying and probably warm stage (5-4 to 3 ka BP) and ending with a cool and dry stage (since 3 ka BP). In the Inner Mongolian Plateau, the early Holocene (from 10.5-9.5 to 8-7.5 ka BP) was warming and dry, and a warm and wet climate occurred from 7.5 to 3.5, during which the best time was 6.3-3.8 ka BP; the climate has been variably drying and probably cooling since 3.5 ka BP. In the northwestern part of the Loess Plateau, several Holocene palaeosols have been identified (10-9, 7.5-5, 4-3 and 2.7-2 ka BP) with the 7.5-5 ka BP palaeosol being most strongly expressed. The best-developed palaeosol-equivalent in major valleys is a swamp-wetland facies deposited between 8885 and 3805 14C yr BP under an extremely wet regime. The climate has fluctuated significantly at least three times around a dry and probably cool regime after the swamp-wetland facies-depositional period. Our summary shows that the Holocene Climatic Optimum occurred nearly contemporaneously (8-5 ka BP) at all sites in the Xinjiang region, in the Inner Mongolian Plateau and in the northwestern part of the Loess Plateau. A warming and wet early Holocene (10-8 ka BP) in the northern Tibetan Plateau is most likely related to high effective soil moisture resulting from snow and ice melting. We propose here that the middle Holocene Climatic Optimum (8-5 ka BP) in arid to semi-arid China was primarily a delayed response of the low latitude oceans to high latitude peak insolation (9-8 ka BP).
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен